ANALISIS YURIDIS ATAS KEWAJIBAN NOTARIS BERSIKAP INDEPENDEN TERHADAP PARA PENGHADAP DITINJAU DARI UU NO. 2 TAHUN 2014 TENTANG PERUBAHAN ATAS UU NO. 30 TAHUN 2004 TENTANG JABATAN NOTARIS - Rika Sofiana; Muhammad Arifin; Ferry Susanto Limbong (STAI Tapaktuan, 2020)
The notary as a public official in carrying out his duties and obligations to make an authentic deed is obliged to act impartially (independent) to the appearers so that the authentic deed made by him avoids legal problems, namely a lawsuit for the cancellation of the authentic deed.This notary does not receive legal sanctions, either administrative sanctions in the form of written warnings, suspension, dismissal with respect and dismissal with disrespect, civil sanctions in the form of compensation claims by the appearers or the injured party for the issuance of the authentic deed, or criminal sanctions in the form of filing a notary public to the police by the injured party and can be sentenced to imprisonment.The obligation to act impartially (independent) to the appearers in making authentic deeds in accordance with the provisions of paragraph 1 of Article 16 of Notary Position Law No. 2 of 2014 concerning amendments to the Notary Position Law No.30 of 2004. The results of this study indicate that the legal criteria for acting impartially for the notary in order to carry out their duties and obligations to make an authentic deed based on the Notary Position Law and notary code of ethics is that the notary must act impartially or neutral towards the appearers, not act as the party in making such authentic deed and not making authentic deed for the benefit of children, wife and family of notaries in lineage.The legal consequence of an authentic deed made by a notary when the notary takes sides in making the authentic notary deed is that the authentic deed is only powerful as a deed not made before an public official, and a lawsuit for cancellation can be submitted to the court by the injured party,and legal sanctions on the contents of the deed containing partiality to one of the parties is that the notary may be subject to administrative sanctions in the form of a written warning, suspension (suspension), dismissal with respect and dismissal with no respect.